Análise da estabilidade funcional de um distrator osteogênico osseosuportado utilizando o método dos elementos finitos - Arantes, Margareth Gomes Rosa (2007)
The distraction osteogenesis is a surgical technique used in the dentistry for the transversal discrepancies correction of the jaw, having as basic principle the intrinsic capacity of some tissue development when submitted to the stress caused by slow and continuous traction. To obtain the osteogenesis success, the distractors osteogenesis symphysianic have to minimize any bone parts displacement. This work had the purpose to evaluate the stability of a distractor symphysis through three-dimensional models of finite elements where different setting positions and different amounts of setting screws are evaluated. The stability was evaluated through the determination of vertical displacements in the load direction in the range of 20 up to 140 N. Additionally; the results of an experimental analysis had been used to adjust the numerical models of finite elements. It was observed that, for the load profile applied, the stability is not a function of setting screws number. The stiffness of the distractor at cut region was the cause of the differences between fixations. In the distractor lower position setting the displacements levels had been lesser, indicating a better distractor stability.